Breaking stereotypes: Psychological conflict of characters in the novel Belenggu by Armijn Pane as a study of modern Indonesian prose - Frika Pamuji; Layli Rahmawati; Kartika Candra Wahyuni; Rizal Hidayat Ramadhan; Risma Dwi Julianti; Suci Fauziyah; Onok Yayang Pamungkas (Journal of Language, Literature, Social and Cultural Studies, 2026)
This study examines the psychological conflicts experienced by the main character in the novel Belenggu by Armijn Pane, as one of the modern Indonesian novels that highlights a lot of human inner upheavals. The purpose of this research is to explain the forms of psychological conflicts that arise, identify the causes of these conflicts, and see how they impact the actions and character development of the characters. This research uses the hermeneutic approach and the literary psychology approach, and utilizes Sigmund Freud's psychoanalytic theory in the data analysis process. The main data of the research is in the form of narrative quotes and dialogues that show the mental state of the characters, such as guilt, anxiety, confusion, emotional dependence, and feelings of emptiness in life. Based on the analysis, it was found that the inner conflicts experienced by Sukartono, Tini, and Yah were influenced by disharmonious domestic relationships, clashes of cultural values, and unmet emotional needs. The conflict then affects the way they make decisions and deal with problems in the story. The results of this study conclude that the novel Belenggu not only presents the problem of love, but also describes the search for identity and the psychological struggle of modern humans in understanding the meaning of life. Therefore, this novel has an important value in literary studies that focus on the psychological aspects of the characters. Keywords: literary psychology, inner conflict, novel Fetters, characters